(untitled) (Research, Society and Development, 2020)
This studio aims to analyze, through microbiological characterization, the water quality of artesian wells located in the city of Acari-RN. The water samples are collected in artesian wells located in the rural area of the city of Acari-RN and can be analyzed in triplicate at the Food Microbiology Laboratory, at the Federal University of Campina Grande, Campus Pombal, Paraíba. The parameters analyzed are: total coliforms, coliform thermotolerants, Escherichia coli, meaning the methodological methods of CETESB (Environmental Company of the State of São Paulo). The determination of the most probable number of coliforms in the mummies is obtained using the multiple tube technique in the series, and the differentiation analysis of coliform thermotolerants is also performed. As a result, the analyzed analyzes show a variation from 320 to 360 NMP.org/100 mL in the return of fecal coliforms, obtaining a similar result for coliform thermotolerants in relation to artesian wells, observing the highest value in artesian well 2 with 240 NMP.org/100 mL, Escherichia coli presents values from <1.4 to <1.9 NMP.org/100 mL, therefore, the analyzed waters do not consider any part of the consumption acquired with Ordinance No. 5/2017 of Ministry of Health to configure the population’s health outcome.